HUBUNGAN SARAPAN PAGI DENGAN ASPEK BIOLOGIS ANAK USIA SEKOLAH - Lamtiur ' Saragi; Oswati ' Hasanah; Nurul ' Huda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract The aim of this research was to identify the relation of breakfast behavior with biological aspect the SDN 26 Pekanbaru’s students the design was correlation research with cross sectional approach. The sampling technigue stratifled random sampling involving 148 elderly that was selected based on inclusion criteria. This research used questionnaire and observation sheet. The univariate and bivariate analysis with chi square test. The result showed that the majority of respondents have good breakfast behavior (54,7%) and the majority respondent have biological aspect problem (70,9%). Farther bivariate analysis showed, there is a correlation between breakfast with biological aspects of school-age children p value (0,000) < alpha (0,05). Keywords: Breakfast, biological aspect, school-age children